Protective effect following intranasal exposure of goats to live Pasteurella multocida B:2 - Saad, Mohd Zamri; Ali, Ernie Zuraida; Mohd Yusoff, Md Sabri (Springer Science + Business Media B.V. 2007, 2006)
This study aimed to determine the effect of intranasal exposure to low doses of Pasteurella multocida B:2 on survival of goats challenged with high doses of the same organism. Eighteen goats were selected and divided into three groups. Goats of group 1 were exposed intranasally twice, with a two-week interval, to 7 × 106 cfu/ml of live P. multocida B:2. Goats of group 2 were not exposed to P. multocida B:2 but were kept together with the exposed group 1. Goats of group 3 remained as unexposed controls and were kept separated from the other two groups. Serum samples were collected at weekly intervals to determine the antibody levels. At week 5 post exposure, all goats were challenged subcutaneously with 3.7 × 1010 cfu/ml of live P. multocida B:2. Following challenge exposure, 8 (67%) goats (4 goats from each of groups 1 and 2) were killed owing to haemorrhagic septicaemia. Four goats were killed peracutely within 48 h post challenge, while the other four goats were killed acutely between 2 and 4 days post challenge. None of the goats of group 3 were killed for haemorrhagic septicaemia. Goats of groups 1 and 2 showed significantly (p < 0.05) higher antibody levels following the first intranasal exposure to P. multocida B:2. However, only group 1 retained the significantly (p < 0.05) high antibody levels following a second intranasal exposure, and remained significantly (p < 0.05) higher than groups 2 and 3 at the time of challenge. P. multocida B:2 was successfully isolated from various organs of goats that were killed between 1 and 4 days post challenge.